Symptoms of Depression and Anxiety Are Independently Associated With Clinical Recurrence of Inflammatory Bowel Disease - Mikocka-Walus, Antonina; Pittet, Valerie; Bauerfeind, Peter; Beglinger, Christoph; Begré, Stefan; Belli, Dominique; Biedermann, Luc; Bigler, Beat; Borovicka, Jan; Bühr, Patrick; Burnand, Bernard; Cremer, Matthias; et al. (Clinical gastroenterology and hepatology, 2016)
We examined the relationship between symptoms of depression and anxiety and clinical recurrence of inflammatory bowel disease (IBD) in a large patient cohort. We considered the progression of depression and anxiety over time. We collected clinical and treatment data on 2007 adult participants of the Swiss IBD study (56% with Crohn’s disease [CD], 48% male) performed in Switzerland from 2006 through 2015. Depression and anxiety symptoms were quantified by using the Hospital Anxiety and Depression Scale. The relationship between depression and anxiety scores and clinical recurrence was analyzed by using survival-time techniques. We found a significant association between symptoms of depression and clinical recurrence over time (for all patients with IBD, P = .000001; for subjects with CD, P = .0007; for subjects with ulcerative colitis, P = .005). There was also a significant relationship between symptoms of anxiety and clinical recurrence over time in all subjects with IBD (P = .0014) and in subjects with CD (P = .031) but not ulcerative colitis (P = .066). In an analysis of a large cohort of subjects with IBD, we found a significant association between symptoms of depression or anxiety and clinical recurrence. Patients with IBD should therefore be screened for clinically relevant levels of depression and anxiety and referred to psychologists or psychiatrists for further evaluation and treatment.